DISCREPANCIES IN THE APPLICATION OF BANKRUPTCY LAW IN AUCTION PRACTICES BY SECURED CREDITORS: LESSONS FROM DECISION No. 15/2023/PN.Niaga.Smg - Maharani, Anindita; Suryanti, Nyulistiowati; Sudaryat, Sudaryat (Universitas Labuhanbatu, 2025)
The execution of collateral by secured creditors is a special right regulated under Article 59 paragraph (1) UU 37/2004, which stipulates that execution may only be carried out no later than two months after the insolvency period begins. However, violations of this provision frequently occur, creating legal uncertainty for bankrupt debtors. This study aims to analyze the judicial considerations in Commercial Court Decision No. 15/Pdt.Sus-Gugatan Lain-lain/2023/PN.Niaga.Smg concerning the determination of the insolvency period and the execution of collateral by secured creditors. Using a normative juridical approach, this research emphasizes secondary data obtained through literature study, analyzed qualitatively. The results show that executions conducted after the insolvency period violate Article 59 paragraph (1) and may constitute an unlawful act. Bankrupt debtors have the right to pursue further legal remedies such as cassation and judicial review. Strengthening regulations and technical guidelines is needed to enhance legal certainty and protection in bankruptcy practice.Keywords: Bankruptcy, Collateral Execution, Insolvency Period